1997
DOI: 10.1042/bj3220937
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction through epidermal growth factor receptor is altered in HeLa monolayer cells during mitosis

Abstract: Epidermal growth factor (EGF)-induced signalling was studied separately in the mitosis and G2-phases of HeLa monolayer cells presynchronized (1) by amethopterin inhibition and thymidine release or (2) by nocodazole. For comparison, cells were treated with the phorbol ester phorbol 12-myristate 13-acetate (PMA). In contrast with the observed responses effected by PMA, which seem to be independent of cell cycle and synchronization conditions, those induced by EGF are greatly influenced by both criteria. Synchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…Recently phosphorylated MEK-1 has been reported to undergo partial proteolysis at the N terminus during mitosis, which results in the inability for MEK1 to interact with and activate ERK1/2 proteins (21). However, it is unlikely that MEK1 is completely uncoupled from ERK1/2 during mitosis because activation of protein kinase C by treatment with phorbol esters can still activate the Raf-1/MEK/ERK pathway in mitotic cells (14). Moreover, we have reported that the observed proteolysis of MEK1 during mitosis may not be because of * The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Recently phosphorylated MEK-1 has been reported to undergo partial proteolysis at the N terminus during mitosis, which results in the inability for MEK1 to interact with and activate ERK1/2 proteins (21). However, it is unlikely that MEK1 is completely uncoupled from ERK1/2 during mitosis because activation of protein kinase C by treatment with phorbol esters can still activate the Raf-1/MEK/ERK pathway in mitotic cells (14). Moreover, we have reported that the observed proteolysis of MEK1 during mitosis may not be because of * The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 92%
“…Similarly, EGF receptor-mediated activation of the ERK pathway is inhibited in mitotic cells (17). In contrast, phorbol ester induction of protein kinase C-mediated signaling pathways has been suggested to be intact in mitotic cells and result in a G 2 -arrest (14,38,39). To explore the mechanisms involved in inactivation of receptor-mediated signaling in mitotic cells, the activation of ERK was compared in cells arrested in mitosis by nocodazole treatment or asynchronous cells following treatment with EGF or PMA.…”
Section: Erk Activity In Mitotic Cells Treated With Egf or Pma-mentioning
confidence: 99%
See 2 more Smart Citations
“…20 Cells were washed with PBS before addition of fresh culture medium to continue the cell cycle. Synchronized cells were examined for their expression of MMP-1 and the cell cycle proteins cdc2 and cyclin B by confocal microscopy and Western blot analysis.…”
Section: Cell-cycle Synchronizationmentioning
confidence: 99%